Estudo de caso sobre decisão de investimentos em empresas de comunicação do Ceará - Bezerra, Tayro Mendonça Lima (2015)
Companies live a new era, where the information is being decentralized, mostly about control and production. The changes affect all sectors of products and services, but especially media companies that are in an increasingly competitive and unpredictable market. The development projects can be the "means" to achieve the sustainability objectives of these companies (SILVA; GIL, 2013). And those responsible for the analysis and approval of these projects are the managers. The objective of this research is to describe the practices used for decision-making on investments in new projects in media companies in Ceará. The survey was conducted on the descriptive qualitative approach; the case study methodology was carried out in-depth interviews with 13 managers of five companies. The results show that the projects can be categorized into two groups: commercial and institutional. They were listed in order of priority the three main factors considered for commercial projects: merchantability advertisers, profitability, and institutional suitability. And the three major factors evaluated in institutional projects: interest of the audience for the content, institutional suitability and technical feasibility. The oriented culture projects were easily perceived during interviews. All managers are clearly targeted, directly or indirectly, to central objectives: expand the audience and expand revenue. TV managers prioritize the appropriateness of the content to the public interest and the production quality. The radio managers must focus on keeping the institutional adjustment of production with high levels of audience. For print media decisions are by financial results. The approval process and decision of the projects is simplified and centralized, although the creation and development is participatory. He emphasized the skill and technical policy for managers in relation to superiors and colleagues, as well as a sense of general responsibility for the financial health of the company. The findings may encourage and contribute to new studies and discussions on the decision-making process in media companies.